GROWTH RESPONSE OF Clarias gariepinus POST-FINGERLINGS TO BLOOD AND DRY POULTRY LITTER MEALS IN UN-EXTRUDED FLOATING FISH FEED - IBIYO, L. M. O; MOGAJI, O. (Nigerian Journal of Fisheries, 2012)
Twelve (12) weeks feeding experiment was conducted at the National Institute for Freshwater Fisheries Research (NIFFR), New Bussa, Niger State, Nigeria. Graded levels (0, 5, 10, 15, 20, 25 or 30) % of dry poultry litter meal (DPLM) and 10% blood meal were fed to post fingerlings of Clarias gariepinus in a completely randomized design with triplicate groups of 27 fish in a (2 m x 2 m x 1 m) concrete tank. Clarias gariepinus responses to the diets showed that there were significant difference in weight gain (WG), feed conversion ratio (FCR), specific growth rate (SGR), survival and nutrient retention (P < 0.05). There was no significant difference between the positive and negative controls with respect to these parameters (P > 0.05). Also, no significant differences were observed between the groups that fed on 5%, 10% and 15% (DPLM) combined with 10% blood meal to replace 15% clupeid fish meal, 5% and 10% wheat offal in the control diet (P > 0.05). The haematological parameters showed slight significant differences (P < 0.05) with generally high levels of lymphocytes in the leukocyte differential analysis (P>0.05). There was also no any pathological defect observed in the fish and no significant difference in palatability of the processed products at the end of the experiment (P > 0.05). The feed cost reduced as DPLM increased and cost N/Kg were N330, 265, 261, 258, 255, 252, 249 and 246 for diet 1, 2, 3, 4, 5, 6, 7 and 8 respectively. It was recommended that 10 - 15% of dry poultry litter from a battery cage system and 10% blood meal can be included into an un-extruded floating fish feed for cost reduction. There is need to carry out such investigation in other freshwater fish species.